Genomic analysis and phylogenetic position of the complex IncC plasmid found in the Spanish monophasic clone of Salmonella enterica serovar Typhimurium - Xenia Vázquez (Nature Portfolio, 2021)
Abstract pUO-STmRV1 is an IncC plasmid discovered in the Spanish clone of the emergent monophasic variant of Salmonella enterica serovar Typhimurium, which has probably contributed to its epidemiological success. The sequence of the entire plasmid determined herein revealed a largely degenerated backbone with accessory DNA incorporated at four different locations. The acquired DNA constitutes more than two-thirds of the pUO-STmRV1 genome and originates from plasmids of different incompatibility groups, including IncF (such as R100 and pSLT, the virulence plasmid specific of S. Typhimurium), IncN and IncI, from the integrative element GIsul2, or from yet unknown sources. In addition to pSLT virulence genes, the plasmid carries genes conferring resistance to widely-used antibiotics and heavy metals, together with a wealth of genetic elements involved in DNA mobility. The latter comprise class 1 integrons, transposons, pseudo-transposons, and insertion sequences, strikingly with 14 copies of IS26, which could have played a crucial role in the assembly of the complex plasmid. Typing of pUO-STmRV1 revealed backbone features characteristically associated with type 1 and type 2 IncC plasmids and could therefore be regarded as a hybrid plasmid. However, a rooted phylogenetic tree based on core genes indicates that it rather belongs to an ancient lineage which diverged at an early stage from the branch leading to most extant IncC plasmids detected so far. pUO-STmRV1 may have evolved at a time when uncontrolled use of antibiotics and biocides favored the accumulation of multiple resistance genes within an IncC backbone. The resulting plasmid thus allowed the Spanish clone to withstand a wide variety of adverse conditions, while simultaneously promoting its own propagation through vertical transmission.